Whole-genome array-CGH for detection of submicroscopic chromosomal imbalances in children with mental retardation - Thuresson, A.-C. (S. Karger AG, 2007)
Chromosomal imbalances are the major cause of mental retardation (MR). Many of these imbalances are caused by submicroscopic deletions or duplications not detected by conventional cytogenetic methods. Microarray-based comparative genomic hybridization (array-CGH) is considered to be superior for the investigation of chromosomal aberrations in children with MR, and has been demonstrated to improve the diagnostic detection rate of these small chromosomal abnormalities. In this study we used 1 Mb genome-wide array-CGH to screen 48 children with MR and congenital malformations for submicroscopic chromosomal imbalances, where the underlying cause was unknown. All children were clinically investigated and subtelomere FISH analysis had been performed in all cases. Suspected microdeletion syndromes such as deletion 22q11.2, Williams-Beuren and Angelman syndromes were excluded before array-CGH analysis was performed. We identified de novo interstitial chromosomal imbalances in two patients (4%), and an interstitial deletion inherited from an affected mother in one patient (2%). In another two of the children (4%), suspected imbalances were detected but were also found in one of the non-affected parents. The yield of identified de novo alterations detected in this study is somewhat less than previously described, and might reflect the importance of which selection criterion of patients to be used before array-CGH analysis is performed. However, array-CGH proved to be a high-quality and reliable tool for genome-wide screening of MR patients of unknown etiology.